Streptococcus pluranimalium meningoencephalitis in a horse. (September 2021) - Fu, Dah-Jiun; Ramachandran, Akhilesh; Miller, Craig
A 3-y-old, female Quarter Horse with a history of acute neurologic signs was found dead and was submitted for postmortem examination. Areas of petechial and ecchymotic hemorrhage were present on cross-sections of the cerebrum, cerebellum, and brainstem. Histologic examination of the brain revealed severe, purulent meningoencephalitis and vasculitis with a myriad of intralesional gram-positive cocci. Streptococcus pluranimalium was identified from formalin-fixed, paraffin-embedded tissue obtained from sites with active lesions by PCR and nucleotide sequencing of bacterial 16S ribosomal RNA. S. pluranimalium should be considered as a cause of meningoencephalitis in a horse.